AB0703 INFLAMMATORY BOWEL DISEASES AMONG SECUKINUMAB-TREATED PATIENTS: FIRST RESULTS OF THE MISSIL REGISTRY. (June 2019) - Letarouilly, Jean-Guillaume; Pariente, Benjamin; Goupille, Philippe; Claudepierre, Pascal; Varin, Stephane; Lanot, Sylvain; Dernis, Emmanuelle; Dantec, Loïc Le; Gaudin, Philippe; Jullien, Denis; Pham, Thao; Flipo, Rene-Marc
Abstract : Background: Interleukin 17 (IL17) blockade is a therapeutic alternative for patients who are Tumor Necrosis Factor inhibitor-Inadequate Responders. However, in randomized controlled trials, cases of de novo inflammatory bowel diseases (IBD) have been reported in patients treated by IL17 inhibitors. Objectives: To describe patients treated by IL 17 inhibitors developing new onset IBD (Crohn's disease and ulcerative colitis). Methods: A French national registry called MISSIL was started in February 2018 to collect the cases of these patients. This registry is conducted by rheumatologist, dermatologist and gastroenterologist learned societies specialized on immune-mediated inflammatory diseases (IMID). In France, secukinumab has been granted market authorization in June 2016 and ixekizumab in april 2018. Results: 12 cases were reported between February and December 2018 : 11 patients with new onset Crohn's disease and one with ulcerative colitis. Mean age was 51 ± 14.3 years old and 8/12 were female. 6 presented an axial spondyloarthritis, 3 a peripheral spondyloarthritis and 3 both. 9/10 were HLA-B27 positive. 4/10 have a radiographic sacroiliitis and 3/10 a MRI sacroiliitis. Only one was biological Disease-modifying antirheumatic drug (bDMARD)-naïve. Crohn's disease was mainly located at the ileum, colon and rectum. The mean time to onset of symptoms was 4.9 ± 5.6 months. The main symptoms were diarrhoea, nausea and vomiting and loss of weight. Median CRP at the onset of symptoms was 107 mg/L (66.5-200.7). 9 patients underwent biopsies. 5 were in favour of Crohn's disease. IL17 inhibitors were consistently stopped. Patients were treated by corticosteroids (9/12), mesalazine (3/12), methotrexate (2/12), thiopurines (1/12), infliximab (3/12), adalimumab (1/12), golimumab (1/12), ustekinumab (3/12). The evolution was favourable under treatment with healing (5/12), improvement (4/12) or stabilization (1/12). One patient worsened under treatment and one died (massive myocardial infarction). Conclusion: IBD under IL 17 inhibitors are rare and lead to discuss the potential iatrogenic role of IL 17 inhibitor drugs. Further cases and case control studies are needed to better characterize this complication and identify patients at risk to develop IBD under IL 17 inhibitor. Disclosure of interests: Jean-Guillaume Letarouilly: None declared, Benjamin Pariente: None declared, Philippe Goupille Grant/research support from: Financial compensation received from MSD on a pro-rota basis for participation in Scientific Committee meetings and functions for this study, Speakers bureau: abbvie, Biogaran, BMS, Hospira, Janssen, MSD, Pﬁzer, Sanoﬁ-Genzyme, UCB, Pascal Claudepierre Consultant for: Honoraria from Novartis as steering committe of this survey, Stephane Varin: None declared, Sylvain Lanot: None declared, Emmanuelle Dernis: None declared, Loïc Le Dantec: None declared, Philippe Gaudin Speakers bureau: Roche, Chugai, BMS, abbvie, Servier, Pfizer, MSD, UCB, ESAOTE, Genévrier, Janssen, Novartis, Lilly, Biogen, amge, Denis Jullien Consultant for: abbott, Celgene, Eli Lilly, Janssen, MSD, Novartis, Pfizer, Serono UCB, Fresenius-Kabi, Biogen, Leo-Pharma and Sandoz, Speakers bureau: abbott, Celgene, Eli Lilly, Janssen, MSD, Novartis, Pfizer, Leo-Pharma, Serono, Thao Pham Speakers bureau: Lilly, Novartis, Rene-Marc Flipo Consultant for: advisory board: Bristol-Myers Squibb